1990
DOI: 10.1159/000129114
|View full text |Cite
|
Sign up to set email alerts
|

Increased Survival Rates by Topical Treatment of Burns with Cerium Nitrate

Abstract: In experiments on mice we were able to show that the negative effects attributed to burn toxins could almost completely be prevented by one single early treatment of the burned skin with a 0.04 M solution of cerium nitrate [Ce(NO3)3]. The survival rate was 10% for animals which were grafted with burned skin. Treatment with Ce(NO3)3 increased the survival rate to 74%. A reflection of this protective effect was the prevention of the burn-induced disturbance of the acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…These results should further improve when successful skin replacement technology becomes clinically available. is now practiced in most large burn units in the United States [ 131. Early excision isvariously defined as early massive excision (i.e., excision of the entire burn wound within 72 hours of injury) [14,15] or more commonly as sequential excision of the entire wound over the first week after injury [5,9,13,16]. Increasing popularity of the prompt excisional approach for management of large burns stems from several documented and perceived advantages over the traditional approach of autografting over granulation after the spontaneous separation of eschar.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results should further improve when successful skin replacement technology becomes clinically available. is now practiced in most large burn units in the United States [ 131. Early excision isvariously defined as early massive excision (i.e., excision of the entire burn wound within 72 hours of injury) [14,15] or more commonly as sequential excision of the entire wound over the first week after injury [5,9,13,16]. Increasing popularity of the prompt excisional approach for management of large burns stems from several documented and perceived advantages over the traditional approach of autografting over granulation after the spontaneous separation of eschar.…”
mentioning
confidence: 99%
“…With early excision in children, burned surface area at which mortality is 50% has been reported to be 95% [20]. There have been studies showing equivocal influences of early excision on survival [14,21]. The incidence of fatal sepsis has been shown to be decreased with early excision [22], but the pattern of mortality does not appear to have been changed with excisional therapy; pneumonia and sepsis-induced organ failures most commonly occur [23].…”
mentioning
confidence: 99%
“…Cerium nitrate is a heavy metal compound that remains under investigation as such a topical burn therapeutic agent. Although it has some antiseptic properties, survival of patients treated with cerium nitrate is greater than would be expected from standard mortality data, and is close to the expected survival of patients who undergo early excision of burn eschar (8)(9)(10)(11)(12). It has been demonstrated that cerium has the ability to bind LPCs responsible for SIRS without binding to collagen or albumen in uninjured skin (13).…”
Section: Cerium Nitratementioning
confidence: 63%
“…Although it has some antiseptic properties, survival of patients treated with cerium nitrate is greater than would be expected from standard mortality data, and is close to the expected survival of patients who undergo early excision of burn eschar (8)(9)(10)(11)(12). It has been demonstrated that cerium has the ability to bind LPCs responsible for SIRS without binding to collagen or albumen in uninjured skin (13). A distinct survival advantage is demonstrated in rodent models following treatment with cerium nitrate, and in humans a survival benefit is conferred by a single cerium nitrate bath on arrival in a unit, followed by standard care (14).…”
Section: Cerium Nitratementioning
confidence: 63%
“…A study in mice receiving skin autografts, which were burned and treated or not with cerium nitrate in vitro, demonstrated the protective effect against the mortality induced by grafting burned skin. Because the observed survival rate was nearly identical to that of burned animals after necrotomy and subsequent skin grafting, the effect of cerium nitrate was considered a chemical equivalent to surgical wound excision and recommended in cases not allowing early surgical intervention (Kistler et al 1990). An impressive reduction of the anticipated death rate following treatment of patients with a single early bathing in aqueous cerium nitrate solution supports this opinion (Scheidegger et al 1992).…”
Section: Antiseptic and Immunomodulatory Properties With Special Refementioning
confidence: 99%